A study of patient's perspectives regarding the adequacy of the informed consent process before a caesarean section - Mayuri Verma; Annie Rajaratnam (CHRISMED Journal of Health and Research, 2023)
Background: A better diagnosis, early referral, and greater health-care coverage have increased cesarean deliveries at tertiary care hospitals in India. While most cesareans are done in good faith, it does not escape the purview of consumer awareness and protection. Our study aims to audit the awareness, understanding, and adequacy among patients about informed consent (IC) before cesarean sections. Materials and Methods: This was a cross-sectional study. A detailed questionnaire was given to 150 postcesarean patients from July 2016 to July 2017. The questionnaire was then evaluated, and the inference was drawn based on the patients' answers. Results: About 84.6% of patients knew the exact indication. About 79.3% were well explained the procedure. Ninety-six percentage were satisfied with the outcome of the procedure. Eighty-four percentage preferred the same institute for their subsequent delivery. Twelve percentage reported that consent was forcibly taken. Ninety-four percentage were unaware about the intraoperative complications. Only 4.6% were explained about the preferred mode of delivery for the next pregnancy. Ninety-two percentage wanted a vaginal delivery for the subsequent pregnancy. Conclusion: Thus, an adequate IC during antenatal visits brings about awareness about the risks and complications of cesarean section and helps better decision-making.